ASSESSMENT OF MICHAEL PORTER’S COMPETITIVE STRATEGIES INFLUENCE ON FINANCIAL PERFORMANCE OF SMALLHOLDER TEA FACTORIES: A CASE OF KIAMBU AND MURANG’A COUNTIES - KIPKOSGEY, ROTICH DOMINIC; SANGORO, MR. OSCAR; OIRERE, Dr. DORCAS; ROMAN, MR. AKETCH (IJRDO - Journal of Business Management, 2016)
The main purpose of this study was to assess Michael Porter’s competitive strategies influence on financial performance of smallholder tea factories in Kenya which has since been liberalised under the category of smallholder tea sub sector in Kenya. The study design used is a descriptive research design to conduct the study, and the study area was Kiambu and Murang’a counties. The target population of the study were tea farmers, tea factory employees and tea factory managers of the study area. The sample studied comprised of twelve smallholder tea factory companies in the tea subsector spread over Kiambu and Murang’a counties in Kenya. The instrumentation used were questionnaires administered to respondents through emails and interview schedules which were used to sought more relevant information and clarify queries in the questionnaire. The research study used both primary and secondary data from sampled respondents. Data was analysed by using of SPSS package version 17, where descriptive and regression model was used to assess the relationship between the variables in the research study.From the findings it was concluded that Cost leadership strategy plays a significant role in determining the financial performance of the smallholder tea factories in Kenya with a beta coefficient of 0.604, the effect is very significant at (p=0.000). Differentiation strategy is useful in making smallholder tea factories’s product stand-out against competitor’s products in the market.